Giải thích các bước giải:
$a.2\frac{3}{29}+\frac{4}{17}-\frac{3}{29}+0,7+\frac{13}{17}=(2\frac{3}{29}-\frac{3}{29})+(\frac{4}{17}+\frac{13}{17})+0,7=2+1+0,7=3,7$
$b.\frac{2}{9}.16\frac{1}{4}-\frac{2}{9}.34\frac{1}{4}=\frac{2}{9}(16\frac{1}{4}-34\frac{1}{4})=\frac{2}{9}.(-18\frac{1}{4})=\frac{-71}{18}$
$c.4.(-\frac{1}{2})^3+\frac{1}{2}=4.\frac{-1}{8}+\frac{1}{2}=\frac{-1}{2}+\frac{1}{2}=0$
$13\frac{1}{3}:(\frac{-2}{5})-27\frac{1}{3}:(\frac{-2}{5})=(13\frac{1}{3}--27\frac{1}{3}):(\frac{-2}{5})=(-14\frac{1}{3}).\frac{-5}{2}=\frac{205}{6}$